2022
DOI: 10.1024/1422-4917/a000816
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Impulsiveness and Internet Use Disorder in Adolescents and Young Adults with Different Main Activities on the Internet

Abstract: Abstract. Objective: Increased impulsiveness is a risk factor for health-endangering behavior patterns. Little is known about whether increased impulsiveness is associated with Internet Use Disorder (IUD) and whether individuals with various main activities on the internet differ in their levels of impulsiveness. Methods: In total, we screened 8,230 vocational students for problematic internet use with the Compulsive Internet Use Scale (CIUS). Participants scoring at least 21 points in the CIUS took part in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Especially low impulse control (or high impulsivity) has been shown to predict compulsive online user behaviour in recent research (Cudo, Torój, Demczuk & Francuz, 2020;Zahrai et al, 2022a;Kattein et al, 2022). Popular self-control theories are dual-system theory (Strack & Deutsch, 2004;Hofmann, Friese & Strack, 2009;) and ego depletion (Baumeister, Bratslavsky, Muraven & Tice, 1998;Muraven & Baumeister, 2000) that also have been referred to in terms of social media and Internet use (e.g., Turel & Qahri-Saremi, 2016;Hofmann, Reinecke & Meier, 2017;Zahrai et al, 2022a).…”
Section: Table Of Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially low impulse control (or high impulsivity) has been shown to predict compulsive online user behaviour in recent research (Cudo, Torój, Demczuk & Francuz, 2020;Zahrai et al, 2022a;Kattein et al, 2022). Popular self-control theories are dual-system theory (Strack & Deutsch, 2004;Hofmann, Friese & Strack, 2009;) and ego depletion (Baumeister, Bratslavsky, Muraven & Tice, 1998;Muraven & Baumeister, 2000) that also have been referred to in terms of social media and Internet use (e.g., Turel & Qahri-Saremi, 2016;Hofmann, Reinecke & Meier, 2017;Zahrai et al, 2022a).…”
Section: Table Of Contentsmentioning
confidence: 99%
“…a higher tendency of giving in to impulses and the failure to be able to resist temptations, was related to more addictive use of Facebook. Kattein et al (2022) investigated adolescents and young adults with more excessive usage patterns regarding Internet use and found that increased impulsiveness was associated with more compulsive Internet use. Soror, Hammer, Steelman, Davis and Limayem (2015) investigated mobile phone use from a dual-systems perspective and found that mobile phone use habit (resembling the impulsive or reflexive system) was significantly and positively associated with both the duration and frequency of mobile phone use, whereas self-regulation (resembling the reflective system) was significantly and negatively associated with these aspects of mobile phone use.…”
Section: Self-control Research: Scales Instances Of Moderation Theore...mentioning
confidence: 99%